Cerebral Arterial Thrombosis in Ulcerative Colitis. (20th June 2013) - Casella, Giovanni; Cortelezzi, Claudio Camillo; Marialuisa, DeLodovici; Cariddi Lucia, Princiotta; Elena Pinuccia, Verrengia; Baldini, Vittorio; Segato, Sergio
Abstract : Thrombosis, mainly venous, is a rare and well-recognized extraintestinal manifestation of inflammatory bowel disease (IBD). We describe a 25-year-old Caucasian man affected by ulcerative colitis and sclerosing cholangitis with an episode of right middle cerebral arterial thrombosis resolved by intraarterial thrombolysis. We perform a brief review of the International Literature.